Numerical Modelling And Validation For Gallium Arsenide / Aluminium Arsenide Of Asymmetric Spacer Layer Tunnel Diode (Aspat)Forterahertz Applications Using Lorentzian –Tsu Esaki Formulation - Effah Binti Jamil (Universiti Sains Islam Malaysia, 2026)
Matric: 3201413 (FKAB)-Restricted until Nov 2028